THE THERMAL STABILITY OF POLYMER CABLE COMPOUNDS WITH A FLAME-RETARDING FILLER - A. Yu. Svatikov; I. D. Simonov-Emelyanov (Тонкие химические технологии)
Currently, halogen-free cable compositions are becoming increasingly common in the manufacture of cable compositions. The concept of halogen-free or “zero halogen” becomes a symbol of fire resistance, low-smoke characteristics, low toxicity of volatile products of combustion, the absence of the toxic, corrosive and irritating gas - hydrogen chloride - and other hydrogen halides in the volatile products. More and more manufacturers of cable products are beginning to pay increasing attention to the problems of processing, toxicity and fire safety. It should be noted that the requirements for improving the fire safety of cable products are constantly becoming tougher, since the main problem of most of these polymeric materials is their flammability, high smoke generation and high flame spread rate. In this regard, there is a burning question to increase these characteristics and bring them to the level of compounds based on PVC. The main way to increase the flame-retardant characteristics of halogenfree cable compositions is to introduce mineral fire retardants into these compositions. The study of the composition and packaging of these mineral fillers-flame retardants makes it possible to increase the level of flame-retardant characteristics of halogen-free cable compositions. The paper presents the results of studies on the thermal stability of cable compositions based on PE + EVA mixtures containing magnesium hydroxide crystalline hydrate as a filler-flame retardant. It is shown that cable compositions containing magnesium hydroxide crystal hydrate are characterized by higher heat resistance and thermal stability (~ 2-fold) compared to a polymeric matrix based on PE + SEVA. This allows to process them at high temperatures (more than 200°C) by extrusion and pressure casting.